178k views
5 votes
How do I solve this​

How do I solve this​-example-1

2 Answers

5 votes

19945.8 to simplify, the answer is

User Kwishnu
by
4.3k points
3 votes


\bf \qquad \qquad \textit{sum of a finite geometric sequence} \\\\ S_n=\displaystyle\sum \limits_(i=1)^(n)\ a_1\cdot r^(i-1)\implies S_n=a_1\left( \cfrac{1-r^n}{1-r} \right)\quad \begin{cases} n=n^(th)\ term\\ a_1=\textit{first term's value}\\ r=\textit{common ratio} \end{cases} \\\\[-0.35em] ~\dotfill


\bf S_(20)=\displaystyle\sum \limits_(n=1)^{\stackrel{\stackrel{n}{\downarrow }}{20}}~\stackrel{\stackrel{a_1}{\downarrow }}{3}(\stackrel{\stackrel{r}{\downarrow }}{1.5})^(n-1)\implies S_(20)=3\left(\cfrac{1-1.5^(20)}{1-1.5} \right)\implies S_(20)=3\left(\cfrac{1-\stackrel{\approx}{3325.3}}{-0.5} \right) \\\\\\ S_(20)=3\left(\cfrac{-3324.3}{-0.5} \right)\implies S_(20)=3(6648.6)\implies S_(20)=19945.8

User Palanik
by
4.7k points